Entrance Porch of the Adinatha or Rishabhnatha Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance porch of the Adinatha or Rishabhnatha Temple, which is a subsidiary shrine in the Bhandasar Temple Complex. The porch has a small dome roof that rests on four pillars. Ornamented with niches, floral motifs and geometric designs, the porch is painted red. The merlons on the exterior wall of this temple are similar to the merlons on the enclosure wall of the temple complex. The building of this porch follows the Rajput style of architecture.